Students' perspective of globalisation in schools on their traditional Asian cultural beliefs and mental well-being. (2nd January 2021) - Diaco, Samuel B.
ABSTRACT: This study explores Asian college students' perspectives on globalisation in the Philippines. It identifies prime indicators of globalisation and the nature and extent of its perceived influences on the students' traditional cultural beliefs and mental well-being. Examined indicators of globalisation include classroom technology, ideologies and behaviours, manners of thinking and making decisions, and outfit styles. The study finds that globalisation is highly rated in many aspects in the learning set-ups that there are epistemological inconsistencies between students' traditional cultural beliefs and the ideologies and behaviours that globalisation promotes, and that the perceived influence of globalisation on mental well-being is negatively associated with the strength of students' traditional cultural beliefs and their levels of mental well-being.